2020
DOI: 10.1101/2020.04.13.039172
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control of mammalian brain aging by the unfolded protein response (UPR)

Abstract: Aging is the major risk factor for the development of dementia and neurodegenerative disorders, and the aging brain manifests severe deficits in buffering capacity by the proteostasis network. Accordingly, we investigated the significance of the unfolded protein response (UPR), a major signaling pathway that copes with endoplasmic reticulum (ER) stress, to normal mammalian brain aging. Genetic disruption of ER stress sensor IRE1α accelerated cognitive and motor dysfunction during aging. Exogenous bolstering of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…These results are in conflict with the idea that the activity of the UPR, and more specifically the IRE1α/XBP1 branch, is attenuated during aging. However, experimental induction of ER stress with pharmacological agents has been shown to result in attenuated UPR signaling in the aging brain compared to young animals (Cabral‐Miranda et al, 2020). It might be possible that the inability to properly engage the UPR in the long‐term produces damage to ER physiology that is compensated for by the upregulation of proteostasis components (ER stress markers) through alternative regulatory pathways.…”
Section: Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…These results are in conflict with the idea that the activity of the UPR, and more specifically the IRE1α/XBP1 branch, is attenuated during aging. However, experimental induction of ER stress with pharmacological agents has been shown to result in attenuated UPR signaling in the aging brain compared to young animals (Cabral‐Miranda et al, 2020). It might be possible that the inability to properly engage the UPR in the long‐term produces damage to ER physiology that is compensated for by the upregulation of proteostasis components (ER stress markers) through alternative regulatory pathways.…”
Section: Perspectivementioning
confidence: 99%
“…It has been reported that the genetic or pharmacological reduction of eIF2α phosphorylation or ATF4/PERK expression improves synaptic plasticity and the performance of animals in memory‐related tasks (reviewed in (Martinez et al, 2018)). Three studies available in the BioRxiv repository might provide the first direct evidence for an involvement of the UPR in normal brain aging (Cabral‐Miranda et al, 2020; Krukowski et al, 2020; Longo et al, 2020). Genetic depletion of PERK in dopaminergic neurons was shown to reduce dopamine release in the striatum on an age‐dependent manner, associated with progressive motor dysfunction (Longo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principle that blocking protein synthesis prevents long-term memory storage was discovered many years ago (22). With age there is a marked decline of protein synthesis in the brain that correlates with defects in proper protein folding (12,(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Age-related decline in memory has been recapitulated in preclinical studies with old rodents ( Chou et al, 2018 ; Yousef et al, 2019 ; Villeda et al, 2011 ; Castellano et al, 2017 ). Specifically, prior studies have identified deficits in spatial memory ( Villeda et al, 2011 ; Villeda et al, 2014 ), working and episodic memory ( Yousef et al, 2019 ; Castellano et al, 2017 ) and recognition memory ( Cabral-Miranda et al, 2020 ), when comparing young, adult mice with older sex-matched animals. The hippocampus is the brain region associated with learning and memory formation and is particularly vulnerable to age-related changes in humans and rodents ( Disterhoft and Oh, 2007 ; McKiernan and Marrone, 2017 ; Oh et al, 2010 ; Rizzo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%